The Role of Matric Potential, Solid Interfacial Chemistry, and Wettability on Isotopic Equilibrium Fractionation - Gaj, M. (2020)
Additionally, we tested two natural soil samples to explore wettability effects. Samples were dried at temperatures between 40 and 550°C to produce chemically modified surface properties. All samples were spiked with water of known isotopic composition at different water contents. The isotopic signature was determined using the vapor‐bag equilibration method. The matric potential of each sample was measured with a soil water potential meter, the contact angle was determined with the sessile drop method, and the surface chemistry by X‐ray photoelectron spectroscopy. In addition to temperature and soil matric potential, the elemental composition has apparently some control on the equilibrium fractionation factor. Based on findings, we introduce a new soil water isotope retention characteristic approach to summarize how these factors (matric potential, contact angle, and soil surface chemistry) each control the equilibrium fractionation factor for 18O/16O and 2H/H. Corresponding retention curve approach parameters are promising to be applied in the future to predict soil water fractionation effects under natural and non‐stationary conditions.